Distractions in digital reading: a meta-analysis of attentional interference effects - Shen, Yamin (Frontiers in Psychology, 2025)
IntroductionDigital reading has become a common learning activity; however, the empirical understanding of how attentional interference affects comprehension remains limited.MethodsThis study employed a meta-analytic approach to synthesize 32 empirical studies investigating the effects of attentional distractors in digital environments. The analysis focused on the overall comprehension effects of attentional distraction in online reading contexts, while examining potential moderating variables including study design, type of attentional distraction, required effort, time control, type of article, participant age, reading device, and time of publication.ResultsThe research results indicate that Hedges’ g is -0.6411, suggesting a negative effect of attentional interference in networked environments on reading comprehension. Moderation analysis further shows that factors such as research design, type of distraction, and educational level influence this effect, particularly in between-subject studies involving television (TV) or music distractions, where older readers experienced greater declines in comprehension.ConclusionThis study advances the understanding of the cognitive-neurological foundations of attention and cognitive load theory, emphasizing the limited capacity of attention in online environments and the need to balance cognitive load to improve reading comprehension. It encourages minimizing distractions such as background music and videos, designing interactive online platforms that promote focus and selfregulated learning, using tools such as eye-tracking to monitor attention, and implementing tailored interventions that help students develop effective selfregulation strategies for better comprehension.